What are the demographic predictors in laparoscopic simulator performance?. Issue 12 (2nd February 2015) - Lin, Diwei; Pena, Guilherme; Field, John; Altree, Meryl; Marlow, Nicholas; Babidge, Wendy; Hewett, Peter; Maddern, Guy
Abstract: Background: Simulation is playing an increasingly important role in surgical education. There are a number of laparoscopic simulators of which the design and tasks vary considerably. It is unknown if any particular type may result in better outcomes for a specific population. This study assesses the predictors of acquisition of basic surgical skills on two different laparoscopic simulators. Methods: Participants ( n = 370) were randomized to be trained and assessed using either a fundamentals of laparoscopic surgery (FLS) or a LapSim (Surgical Science, Goteborg, Sweden) simulator. The number of attempts required to reach proficiency on individual tasks and on each simulator was recorded and compared with demographic data and surgical experience. Result: Skills acquisition on both simulators was positively affected by surgical experience. Gender was an influential factor on the LapSim with men reaching proficiency sooner than women. The effect of gaming had no clear influence on the participants' scores; however, for those who reported more than 1 h/week gaming, it had a positive influence on skills acquisition on the FLS and a negative influence on the LapSim. Playing a musical instrument had no impact. Practising non‐surgical tasks requiring manual dexterity and handedness were not an influential factor in total proficient scores, but had a significant impact on individual task scores on the FLS simulator. Conclusions: The rate of skills acquisition on each simulator and individual tasks are influenced by different demographic characteristics of the participants. This has implications for surgical education as it may inform the selection of the most suitable laparoscopic simulators for specific populations of trainees.